(untitled) (Physical Education, Health and Social Sciences, 2025)
The goal of this research is to learn about the ways in which the mental processes and creative abilities of university students are influenced by their imaginations and mindsets. Mindset encompassing beliefs about intelligence to influence imaginative thinking. Positivism was the research paradigm in this study. The data was collected using a quantitative research method and utilized a causal-comparative research strategy. The 640 universities students were chosen for the study using a purposive selection method. Two sections of the modified instrument were used: the first with demographics, and the second had 49 items, 29 about mindset and had a reliability of.877; the second half had 20 items dealing with imagination and had a reliability of.876). Three specialists verified the accuracy of the instrument. Analyses of the data were conducted using descriptive and inferential statistics. The results showed that mentality had a moderately beneficial effect on creativity. This research was conducted through survey method and it’s beyond the control of researcher. The findings indicated that there was a rather weak positive association between mindset and the imagination of the students. Implication: This will strengthen the learning approaches of students and expose them to various assignments with the aim of doing best and therefore their assessment and personal virtues will mature as a result of which their potential will be developed accordingly and as a result prefer a better career.